Policy Implementation of Direct Cash Assistance Based on DTKS and P3KE Desil 1 in Langowan Timur District - Lumingkewas, Donald J. K.; Kairupan, Sisca Beatrix; Tarore, Steven V. (JR Education, 2025)
This study examines the implementation of the Direct Cash Assistance (BLT) policy based on the Integrated Social Welfare Data (DTKS) and the Desil 1 of the Extreme Poverty Eradication Acceleration Program (P3KE) in Langowan Timur District, Minahasa Regency. Using a qualitative descriptive approach, this research explores four key variables from the Van Meter and Van Horn (1975) policy implementation model: policy standards and objectives, resources, inter-organizational communication and coordination, and disposition of implementers. Data were collected through interviews, observations, and documentation involving stakeholders, including village officials, community leaders, and aid recipients. Findings reveal that although the program generally aligns with its regulatory framework, several challenges persist, particularly in data accuracy, coordination among institutions, and infrastructure limitations. The study offers recommendations for improving the quality of data, enhancing community participation, and strengthening institutional capacity to ensure more equitable and effective policy implementation.